Keeping born-digital literary and artistic archives in an imperfect world: theory, best practice and good enoughs. Issue 1 (November 2018) - Gurciullo, Sebastian
Abstract : Born-digital literary and artistic archives present interesting challenges. Their creators are people who are seeking an audience and therefore might have a concern for how they are viewed by posterity, but the limited means and motivation for many and the idiosyncrasies of their creative processes might lead them to neglect their digital records. Much of the advice developed for the keeping of electronic records has emerged from the corporate sector and has in mind the kind of expertise and guidance applied at relatively early stages of managing records. These conditions do not apply to the realm of personal records. Archival theory and practice relating to personal records will be explored, along with emerging fields of study such as personal digital archiving (PDA) emphasizing actual behaviour in electronic records environments. The problem of benign neglect will be central to this discussion and the exploration of minimalist interventions that can offset its most egregious effects, particularly through tailored outreach to early career artists and writers. Approaches that will contend with the inevitably imperfect archives that will arrive at archival institutions will also be briefly considered.